IMPLEMENTATION OF TEBING TINGGI CITY REGIONAL REGULATION NUMBER 01 OF 2020 CONCERNING REGIONAL TAXES (SPECIFICALLY ON TEBING TINGGI CITY ENTERTAINMENT TAX) - Aidhil Rahmad Dalimunthe; Subhihar; Heri Kusmanto (Journal of International Islamic Law, Human Right and Public Policy, 2024)
National development in Indonesia is carried out by adhering to the principle of regional autonomy. Regional autonomy allows local governments to regulate all regional interests, one of which is related to regional development financing. The main source of regional financing comes from Regional Original Revenue (PAD). The largest PAD revenue comes from regional taxes. The regional tax revenue target is determined by the Regional Financial and Revenue Management Agency (BPKPD). However, in the period 2021-2023, the effectiveness of entertainment tax revenue in Tebing Tinggi City is below 50%. This study aims to analyze the implementation and inhibiting factors for the implementation of Tebing Tinggi City Regional Regulation Number 01 of 2020 concerning Regional Taxes in optimizing the entertainment tax of Tebing Tinggi City. The research method used was qualitative descriptive and data was collected through interviews and documentation with a total of 14 informants. The results of the study show that: (1) The implementation is carried out quite well but is still not optimal due to the emergence of inhibiting factors from the BPKPD and entertainment taxpayers; (2) Factors inhibiting the implementation include the slow issuance of SPTPD, the inadequate number of officers, the different locations of registration with tax payments, the lack of information dissemination, the lack of facilities and infrastructure, and the lack of understanding of taxpayers.